An emotional journey : from sensory attributes to packaging and back again! - Ng, May Ling (2013)
With the rapid proliferation of new products into the marketplace, understanding emotional responses may offer a differential advantage beyond traditional hedonic measures. Thomson et al. (2010) argued that consumers also associate other functional connotations (e.g. refreshing) and abstract feelings (e.g. sophisticated) to a product, referring to these associations (emotional, abstract and functional) as 'conceptualisations'. The aim of this project was to investigate the effect of the sensory attributes and packaging cues of commercial blackcurrant squashes on consumers' liking and conceptualisations. Initially, the sensory attributes of the squashes were characterised using a sequential approach of quantitative descriptive analysis (QDA) and temporal dominance of sensations (TDS). Using QDA and TDS in tandem was revealed to be more beneficial than each on its own, providing a fuller sensory profile. Next, emotional response and liking within the squash category was measured using the EsSense Profile TM, in which consumers rated a predefined emotion lexicon (n=100) under three conditions: (1) blind, (2) pack and (3) informed (product and packaging). The project also measured how emotional, abstract and functional responses changed across blind, pack and informed conditions. A conceptual lexicon was defined by consumers (n=29), after which a different group of subjects (n=100) rated the squashes using the lexicon and a check-all-that-apply (CATA) approach (CD-CATA). The findings of both EsSense Profile and CD-CATA experiments revealed that intrinsic sensory attributes had more association with emotions and liking, than the packaging. Interestingly, the CD-CATA experiment suggested that extrinsic packaging cues had more association with abstract/functional conceptual responses. The relationship between liking and emotional responses to debranded squash (sensory attributes) was investigated comparing EsSense Profile and CD-CATA approaches. Both approaches yielded emotional data that clearly discriminated across the products more effectively than the hedonic scores. In addition, both approaches produced similar emotional spaces and product configurations. A two dimensional structure (pleasantness vs. engagement/activation) corresponding to published circumplex emotion models was observed in each method. The final phase of the PhD was to determine the relationship between sensory attributes of the squashes (as measured by QDA and TDS) and consumer responses (EsSense Profile and CD-CATA approaches). Sensory attributes in squashes that were found to drive liking and positive conceptual responses in consumers were 'natural processed blackcurrant' and 'natural sweetness'. The study also shows how some temporally dominant sensory attributes (e.g. 'minty') evoked positive conceptual responses in consumers. Throughout the thesis, recommendations regarding practical implications for emotion measurement and general ideas for future research are discussed.